Peat water electrocoagulator design with aluminium electrodes in household scale for cleaning water supply - Hadary, Ferry; Rezeki, Sri; Dewi, Sri Utari Shinta; Alana, Darul Giring; Anindito, Adith; Yulianto, Supi; Gumilar, Desisius; Putri, Lisa Astridni; Hansen (Communications in Science and Technology, 2025)
The peat water studied contained colour, turbidity, organic substances, and iron that were sufficient to be analysed for the use of electrocoagulation. The aluminium electrodes were contacted with peat water by varying electrode plates, sedimentation time, electrolyte concentration, stirring speed, and contact time to produce clean water. The results showed that the electrocoagulator with the 3 pairs of electrode plates, 60-minute sedimentation time, 75 g NaCl electrolyte concentration, stirring speed at 75 rpm, and 60-minute electrocoagulation time was the most optimal variation. The results showed that the electrocoagulation method was able to reduce the pollutant levels in peat water. The results of this treatment also met the standards of the Ministry of Health and based on the calculation of cost incurred by the electrocoagulation method, i.e. $ 0.154/day, $ 4.641/month and $ 55.693/year.